The Motives of Death in B. Chobanzade’s Lyrical and Journalistic Diary “The Song of the Reed-Pipe” and its Place in the Context of the Author’s Creative Explorations - Tair Kirimov (Крымское историческое обозрение)
Based on the materials of the artistic day book “Song of the Reed-Pipe”, the poetics of the early work of Bekir Chobanzade, one of the brightest representatives of the Crimean Tatar literature of 1917–1920, is thoroughly considered. This is the time of political, revolutionary upheavals; the formation of the people’s liberation movement of Muslims in the Crimea; the convocation of the First Democratic Kurultai, which proclaimed: the restoration of equal rights for women, the abolition of class privileges, the allotment of peasants with land, the idea of founding national and cultural autonomy. “Reed-Pipe Songs” were written by the author during his studies in Hungary and Switzerland. Loneliness, longing after ancestral home, worries about the fate of the motherland, the search for the meaning of life occupy the main place in his creative heritage. Selfless struggle and heroic death for the freedom of the people in the understanding of B. Chobanzade are the meaning of the life of every Tatar. He prays to the Almighty for a glorious death for himself and a life full of suffering for his enemies. Pessimistic romanticism, civic spirit determine the creative character of the writer. Despite the fact that B. Chobanzade is known as a major specialist in the study of languages and literatures of the Turkic peoples, his literary personality has been studied only in a perfunctory manner. The main reason for this is the complex imagery of the language of the works, the depth of the author’s philosophical thought based on national traditions and mythology. The works of previous researchers of the life and creative path of the cultural actor are analyzed. The main linguistic, generic-topical, stylistic features of the literary texts of the mentioned collection are revealed. The philosophical and aesthetic component of the motives of death in the works of B. Chobanzade is comprehended.